Tachycardic and non-tachycardic responses in trauma patients with haemorrhagic injuries. Issue 9 (September 2018) - Reisner, Andrew T.; Edla, Shwetha; Liu, Jianbo; Liu, Jiankun; Khitrov, Maxim Y.; Reifman, Jaques
Abstract: Background: Analyses of large databases have demonstrated that the association between heart rate (HR) and blood loss is weaker than what is taught by Advanced Trauma Life Support training. However, those studies had limited ability to generate a more descriptive paradigm, because they only examined a single HR value per patient. Methods: In a comparative, retrospective analysis, we studied the temporal characteristics of HR through time in adult trauma patients with haemorrhage, based on documented injuries and transfusion of ≥3 units of red blood cells (RBCs). We analysed archived vital-sign data of up to 60 min during either pre-hospital or emergency department care. Results: We identified 133 trauma patients who met the inclusion criteria for major haemorrhage and 1640 control patients without haemorrhage. There were 55 haemorrhage patients with a normal median HR and 78 with tachycardia. Median ΔHR was −0.8 and +0.7 bpm per 10 min, respectively. Median time to documented hypotension was 8 and 5 min, respectively. RBCs were not significantly different; median volumes were 6 (IQR: 4–13) and 10 units (IQR: 5–16), respectively. Time-to-hypotension and mortality were not significantly different. Tachycardic patients were significantly younger (P < 0.05). Only 10 patients with normal HR developed transient/temporary tachycardia, and only 11 tachycardic patients developed a transient/temporary normal HR. Conclusions: The current analysis suggests that some trauma patients with haemorrhage are continuously tachycardic while others have a normal HR. For both cohorts, hypotension typically develops within 30 min, without any consistent temporal increases or trends in HR.